Improvement of the Solar Photoelectric System Installed to Cover 30 Percent of the Electricity Consumption of Administrative Buildings - Mirzayev Akhror Abdullayevich; Murtazayeva Fayyoza Mirjahan qizi (Genius Journals, 2023)
This article provides information aimed at covering the buildings of ministries and state organizations with solar panels using energy-saving and renewable energy sources and reducing energy consumption in these organizations and it is recommended to use ongrid photoelectric systems to reduce energy consumption.
Keywords: solar energy; on-grid; photovoltaic system